Good Glycemic Control Is Associated with Better Survival in Diabetic Patients on Peritoneal Dialysis: A Prospective Observational Study - Yoo, Dong Eun (Public Library of Science, 2012)
BACKGROUND: The effect of glycemic control after starting peritoneal dialysis (PD) on the survival of diabetic PD patients has largely been unexplored, especially in Asian population. METHODS: We conducted a prospective observational study, in which 140 incident PD patients with diabetes were recruited. Patients were divided into tertiles according to the means of quarterly HbA1C levels measured during the first year after starting PD. We examined the association between HbA1C and all-cause mortality using Cox proportional hazards models. RESULTS: The mean age was 58.7 years, 59.3% were male, and the mean follow-up duration was 3.5 years (range 0.4–9.5 years). The mean HbA1C levels were 6.3%, 7.1%, and 8.5% in the 1(st), 2(nd), and 3(rd) tertiles, respectively. Compared to the 1(st) tertile, the all-cause mortality rates were higher in the 2(nd) [hazard ratio (HR), 4.16; 95% confidence interval (CI), 0.91–18.94; p = 0.065] and significantly higher in the 3(rd) (HR, 13.16; 95% CI, 2.67–64.92; p = 0.002) tertiles (p for trend = 0.005), after adjusting for confounding factors. Cardiovascular mortality, however, did not differ significantly among the tertiles (p for trend = 0.682). In contrast, non-cardiovascular deaths, most of which were caused by infection, were more frequent in the 2(nd) (HR, 7.67; 95% CI, 0.68–86.37; p = 0.099) and the 3(rd) (HR, 51.24; 95% CI, 3.85–681.35; p = 0.003) tertiles than the 1(st) tertile (p for trend = 0.007). CONCLUSIONS: Poor glycemic control is associated with high mortality rates in diabetic PD patients, suggesting that better glycemic control may improve the outcomes of these patients.